Obesity and Obesity-Related Comorbidities in a Canadian First Nation Population**This article is part of a joint publication initiative between Preventing Chronic Disease and Chronic Diseases in Canada. Preventing Chronic Disease is the primary publisher, while Chronic Diseases in Canada is the secondary publisher. - Bruce, Sharon G.; Riediger, Natalie D.; Zacharias, James M.; Kue Young, T.
Introduction Rates of obesity are higher among Canada's Aboriginal First Nations populations than among non-First Nations populations. We studied obesity and obesity-related illness in a Manitoba First Nation community. Methods We conducted a screening study of diabetes and diabetes complications in 2003, from which we drew a representative sample of Manitoba First Nations adults (N = 483). We assessed chronic disease and chronic disease risk factors. Results Prevalence of obesity and associated comorbidities was higher among women than men. By using multivariate analysis, we found that factors significantly associated with obesity among women were diastolic blood pressure, insulin resistance, and employment status. Among men, factors were age, apolipoprotein A1 level, apolipoprotein B level, and insulin resistance. Seventy-five percent of study participants had at least 1 of the following conditions: obesity, dyslipidemia, hypertension, or diabetes. Comorbidity was high even among the youngest age groups; 22% of men and 43% of women aged 18 to 29 had 2 or more chronic conditions. Twenty-two percent of participants had undiagnosed hypertension. Participants with undiagnosed hypertension had significantly more chronic conditions and were more likely to have microalbuminuria than were those without hypertension. The number of chronic conditions was not significantly different for participants with newly diagnosed hypertension than for those with previously diagnosed hypertension. Conclusions The prevalence of obesity and other chronic conditions in the study community is high, especially considering the number of young people. Community-based interventions are being undertaken to reduce the excessive rate of illness.